Features of sea ice motion observed with ice buoys from the central Arctic Ocean to Fram Strait - Hongwei, Han; Ruibo, Lei; Peng, Lu; Zhijun, Li (Polar Research Institute of China - PRIC, 2020)
Using six ice-tethered buoys deployed in 2012, we analyzed sea ice motion in the central Arctic Ocean and Fram Strait. The two-hourly buoy-derived ice velocities had a magnitude range of 0.01–0.80 m·s−1, although ice velocities within the Arctic Basin were generally less than 0.4 m·s−1. Complex Fourier transformation showed that the amplitudes of the sea ice velocities had a non-symmetric inertial oscillation. These inertial oscillations were characterized by a strong peak at a frequency of approximately −2 cycle·d−1 on the Fourier velocity spectrum. Wind was a main driving force for ice motion, characterized by a linear relationship between ice velocity and 10-m wind speed. Typically, the ice velocity was about 1.4% of the 10-m wind speed. Our analysis of ice velocity and skin temperature showed that ice velocity increased by nearly 2% with each 10 ℃ increase in skin temperature. This was likely related to weakened ice strength under increasing temperature. The ice-wind turning angle was also correlated with 10-m wind speed and skin temperature. When the wind speed was less than 12 m·s−1 or skin temperature was less than −30 ℃, the ice-wind turning angle decreased with either increasing wind speed or skin temperature. Clearly, sea ice drift in the central Arctic Ocean and Fram Strait is dependent upon seasonal changes in both temperature and wind speed.